Teaching Grammar Through Project based Learning: Empowering Students' English Proficiency - Nurlely, Ledy (Journal of English Education Forum (JEEF), 2024)
Project based Learning (PjBL), which emphasizes experiential learning, introduces a contrast between the structure of grammar and the open-ended nature of projects. This combination offers teachers with numerous hurdles, changing standard grammar education paradigms. English communication is essential in an increasingly international society. This study investigates the difficulties in incorporating PjBL into English grammar instruction in higher education. It investigates the contradictions between structured grammar and project flexibility, reconciling thorough comprehension with project constraints, and cultivating both grammar mastery and critical thinking. Managing time restrictions and providing direction are critical concerns. To overcome these obstacles, projects must be aligned with curriculum goals, and resources must be available to assist students' investigation. Virtual project experiences via learning platforms and Web 2.0 tools are among the future directions. The success of grammar projects is dependent on proper topic selection, skill integration, and proficiency alignment. They go beyond solitary practice by immersing pupils in real-life language skills. This comprehensive approach connects theoretical grammar understanding with practical language application. Finally, the combination of PjBL and grammar instruction brings education into a new era of transformation. This trip enriches language training by providing learners with communication skills and problem-solving abilities in preparation for the dynamic world ahead.